Optimal operating scenario for Polerood hydropower station to maximize peak shaving and produced profit - Forouzi Feshalami, Behzad (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
This paper deals with the optimization of the daily operation of Polerood hydropower station being constructed in the north of Iran. Dynamic Programming method (DP) is applied as the preferred optimization tool owing to the fact that it guarantees the optimal solution and is applicable to the present problem. Produced profit and peak-shaving are the two objectives considered separately in this study. The results show that the optimal water management of the case study through charging and discharging the reservoir at the appropriate times led to 4% increase in the produced profit. In another part of this study, the optimal performance strategies regarding to the two objectives (produced profit and peak-shaving) are compared. The observed similarity between the two performance strategies implies the substantial dependence of the electricity price and the network demand level. The paper ends with the profitability study of the project and the sensitivity analysis of the results to various economic parameters.Â Article History: Received December 15th 2017; Received in revised form April 18th 2018; Accepted September 16th 2018; Available onlineHow to Cite This Article: Feshalami, B.F. (2018) Optimal Operating Scenario for Polerood Hydropower Station to Maximize Peak Shaving and Produced Profit. International Journal of Renewable Energy Development, 7(3), 233-239.https://doi.org/10.14710/ijred.7.3.233-239